Functional Outcomes and Reading Speeds following PRESBYOND LBV Using Nonlinear Aspheric Ablation Profiles Combined with Micro-Monovision - Sheetal Brar; Smith Snehal Sute; Sheetal N. Bagare; Sri Ganesh (Journal of Ophthalmology)
Purpose. To report the functional outcomes and reading speeds following PRESBYOND laser blended vision (LBV) using nonlinear aspheric ablation profiles with micro-monovision with the Carl Zeiss Meditec MEL 90 platform. Methods. Data have been collected retrospectively for all patients who underwent PRESBYOND LBV using the MEL 90 excimer laser. Postoperative binocular uncorrected distance and near visual acuity, stereo-acuity, contrast sensitivity, and reading performance were compared with pre-op values measured with patient’s progressive glasses. Mean follow-up was 6 ± 1.2 months. Results. Sixty eyes of 30 patients (mean age 50.47 ± 6.43 years) were included. Of these, 18 patients were hyperopic and 12 patients were myopic with mean SE of 1.28 ± 1.38 D and −2.84 ± 1.86 D, respectively. At 6 months, the mean binocular UDVA was ≥−0.03 ± 0.06 log MAR and the mean binocular UNVA was ≥0.22 ± 0.04 log MAR. The uncorrected reading speeds (words per minute) at the preferred reading distance of 46.17 cm, 60 cm, and 80 cm were significantly better (p value <0.01), whereas the smallest letter size and reading acuities were comparable to the preoperative values (p>0.05 for all distances). Uncorrected contrast sensitivity log values showed mild reduction; however, this was not statistically significant for any spatial frequency. There was a significant reduction in post uncorrected stereopsis to 89.67 arc sec, compared with pre-op corrected stereopsis (50.67 arc sec); however, it recovered fully with near correction (53.33 arc sec, p>0.05 compared with pre). Conclusion. PRESBYOND LBV resulted in significantly better reading speeds and satisfactory functional visual outcomes, without a permanent change in stereo-acuity and contrast sensitivity 6 months postoperatively.